Aplikasi Fenton – Fotokatalisis TiO2 pada Pengolahan Air Gambut - Kasanudin, Ahmad; Yuliawati, Erna; Fernianti, Dewi (Jurnal Teknologi Riset Terapan, 2024)
Purpose: This study investigated the effectiveness of combining the Fenton process with TiO? photocatalysis to improve peat water quality by reducing TSS, BOD, Fe, color, and bacterial contamination. Methodology: Peat water samples were treated in a batch reactor using TiO? doses of 1.5 g and 2.5 g under UV exposure for 2, 4, and 6 h. Hydrogen peroxide (H?O?) and TiO? served as oxidants and photocatalysts, respectively. The parameters measured before and after treatment included TSS, BOD, Fe, pH, color, and E. coli. Results: The best performance was achieved with 2.5 g TiO? and 4 h of UV exposure, reducing BOD to 1.65 mg/L, TSS to 17.8 mg/L, Fe to 0.36 mg/L, and fully eliminating E. coli. However, the pH remained acidic at 2.93. The process was effective in removing pollutants and disinfecting water, although it was insufficient for pH neutralization. Conclusion: The combined Fenton–TiO? process significantly enhanced peat water treatment by reducing major pollutants and bacterial contamination. Optimal results were achieved with 2.5 g TiO? and 4-hour UV exposure, but further treatment is required to raise the pH to potable standards. Limitations: The process failed to achieve neutral pH levels and was tested only in a laboratory-scale setting, without evaluating real-world scalability. Contribution: This study supports the use of Fenton–TiO? photocatalysis as a promising method for treating heavily polluted peat water. This study provides operational insights for the development of advanced oxidation-based systems for sustainable water purification.